Androgen-responsive FOXP4 is a target for endometrial carcinoma - Kayo Kayahashi; Mahadi Hasan; Anowara Khatun; Susumu Kohno; Jumpei Terakawa; Shin-ichi Horike; Natsumi Toyoda; Ayumi Matsuoka; Takashi Iizuka; Takeshi Obata; Masanori Ono; Yasunari Mizumoto; et al. (Communications Biology, 2024)
Abstract Although low estrogen is considered to suppress uterine endometrial carcinoma, the most cases occur in the postmenopausal stage. After menopause, the production of androgen level also declines. Therefore, to resolve the above enigma, we hypothesize that the postmenopausal decline of androgen is a trigger of its progression. In the present study, to validate this hypothesis, we examine the pathological roles of androgen/AR by analyzing clinical data, culturing endometrioid cancer cell lines, and using murine models. Clinical data show that androgen receptor (AR) expression and serum dihydrotestosterone (DHT) are associated with lower disease-free survival (DFS). DHT suppresses malignant behaviors in AR-transfected human endometrial cancer cells (ECC). In ovariectomized Pten ff /PR cre/+ mice, DHT decreases the proliferation of spontaneously developed murine ECC. In AR-transfected human ECC and Pten ff /PR cre/+ mice, DHT suppresses FOXP4 expression. FOXP4-overexpressed human ECC increases, while FOXP4-knocked-down ECC shows decreased malignant behaviors. DHT/AR-mediated ECC suppression is restored by FOXP4 overexpression. The high FOXP4 expression is significantly correlated with low postoperative DFS. These findings indicate that the androgen/AR system suppresses the malignant activity of endometrial carcinoma and that downstream FOXP4 is another target molecule. These findings will also impact developments in clinical approaches to elderly health.